Standard procedures for the diagnostic pathway of sleep‐related epilepsies and comorbid sleep disorders: A European Academy of Neurology, European Sleep Research Society and International League against Epilepsy‐Europe consensus review. (21st September 2020) - Nobili, Lino; de Weerd, Al; Rubboli, Guido; Beniczky, Sándor; Derry, Christopher; Eriksson, Sofia; Halasz, Peter; Högl, Birgit; Santamaria, Joan; Khatami, Ramin; Ryvlin, Philippe; Rémi, Jan; et al.
Abstract: Background: Some epilepsy syndromes (sleep‐related epilepsies [SRE]) have a strong link with sleep. Comorbid sleep disorders are common in patients with SRE and can exert a negative impact on seizure control and quality of life. Purposes: To define the standard procedures for the diagnostic pathway of patients with possible SRE (scenario 1) and the general management of patients with SRE and comorbidity with sleep disorders (scenario 2). Methods: The project was conducted under the auspices of the European Academy of Neurology (EAN), the European Sleep Research Society (ESRS) and the International League against Epilepsy (ILAE) Europe. The framework of the document entailed the following phases: conception of the clinical scenarios; literature review; statements regarding the standard procedures. For literature search a step‐wise approach starting from systematic reviews to primary studies was applied. Published studies were identified from the National Library of Medicine's MEDLINE database and Cochrane Library. Results: Scenario 1: despite a low quality of evidence, recommendations on anamnestic evaluation, tools for capturing the event at home or in the laboratory are provided for specific SRE. Scenario 2: Early diagnosis and treatment of sleep disorders (especially respiratory disorders) in patients with SRE are likely to be beneficial for seizures control. Conclusions: Definitive procedures for evaluating patients with SRE are lacking. We provide advice that could be of help for standardising and improving the diagnostic approach of specific SRE. The importance of identifying and treating specific sleep disorders for the management and outcome of patients with SRE is underlined.